PENGGUNAAN ALAT PERAGA MANIK – MANIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMP NEGERI SOKORIA - Maria Katarina Badhi; Sofia Sa'o; Finsensius Yesekiel Naja (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2020)
The purpose of this study is to find out the activities and learning outcomes of students on integer operating materials using beaded props. The type of research used is PTK research. The population used is all students of Grade Vll Grade SMP Sokoria, and the sample in this study was 20 Students of Class Vll SMP Negri Sokoria. The data analysis technique used is a descriptive statistic analysis. Based on activities in cycle I and cycle II, the percentage of students' learning outcomes increased, namely cycle I students who completed only 13 people or with a percentage of 65% while those who had not completed 7 people or with a percentage of 35%. While in cycle II students completed 20 people or with a percentage of 100%. From cycle I and cycle II, it can be concluded that the percentage of students' learning outcomes increase from 13 complete people to 20, complete people. All students sampled in this study achieved KKM scores.